2020
DOI: 10.1371/journal.pone.0229807
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitat and ectomycorrhizal effects on the establishment, growth and survival of Quercus ilex L. seedlings under drought

Abstract: The success of tree recruitment in Mediterranean holm oak (Quercus ilex) forests is threatened by the increasing intensity, duration and frequency of drought periods. Seedling germination and growth are modulated by complex interactions between abiotic (microhabitat conditions) and biotic factors (mycorrhiza association) that may mitigate the impacts of climate change on tree recruitment. To better understand and anticipate these effects, we conducted a germination experiment in a long-term precipitation reduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 52 publications
0
14
1
Order By: Relevance
“…Seedlings represent a demographic bottleneck for natural regeneration, and are exceptional in many aspects of their structure and function. Several studies point to extensive mortality rates in the first year, with peaks shortly after germination and/or during summer drought (Johnson & Smith, 2005;Johnson et al, 2011;Reinhardt et al, 2015;Augustine & Reinhardt, 2019;Garcia de Jalon et al, 2020;Miller et al, 2020), due at least in part to limited photosynthetic carbon gain and drought stress (e.g. Germino et al, 2002;Fenner & Thompson, 2005;Reinhardt et al, 2015;Brodersen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Seedlings represent a demographic bottleneck for natural regeneration, and are exceptional in many aspects of their structure and function. Several studies point to extensive mortality rates in the first year, with peaks shortly after germination and/or during summer drought (Johnson & Smith, 2005;Johnson et al, 2011;Reinhardt et al, 2015;Augustine & Reinhardt, 2019;Garcia de Jalon et al, 2020;Miller et al, 2020), due at least in part to limited photosynthetic carbon gain and drought stress (e.g. Germino et al, 2002;Fenner & Thompson, 2005;Reinhardt et al, 2015;Brodersen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Beniwal et al, 2010;Sebastiana et al, 2019), although the experimental findings on drought effects can be quite mixed (Lehto & Zwiazek, 2011). Water stress did increase oak EcM colonization in some studies (Dixon et al, 1980;Garcia de Jalon et al, 2020), although the opposite was also reported (poplar; Beniwal et al, 2010). As previous studies suggested, the actual response can be highly specific to the combination of fungi species, hosts and experimental conditions.…”
Section: Discussionmentioning
confidence: 86%
“…Mediterranean forests are prone to relatively frequent environmental changes (Petit et al, 2005). The effects of these changes, which are often the result of fires (Glassman et al, 2016) or droughts (García de Jalón et al, 2020), might be mitigated by the ectomycorrhizal fungal community that had evolved in these habitats. Aleppo pine (Pinus halepensis Miller) is the most common forest tree species around the Mediterranean (Ne'eman & Osem, 2021) and is well adapted to local conditions (Klein et al, 2011;Voltas et al, 2018;Patsiou et al, 2020).…”
Section: Methodsmentioning
confidence: 99%